2021
DOI: 10.3390/ijms22137084
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Insulin-Like Growth Factor 1 and Nerve Growth Factor in Alzheimer’s Disease-Like Pathology and Survival Role of the Mix of Embryonic Proteoglycans: Electrophysiological Fingerprint, Structural Changes and Regulatory Effects on Neurotrophins

Abstract: Alzheimer’s disease (AD)-associated neurodegeneration is triggered by different fragments of amyloid beta (Aβ). Among them, Aβ (25-35) fragment plays a critical role in the development of neurodegeneration—it reduces synaptic integrity by disruption of excitatory/inhibitory ratio across networks and alters the growth factors synthesis. Thus, in this study, we aimed to identify the involvement of neurotrophic factors—the insulin-like growth factor 1 (IGF-1) and nerve growth factor (NGF)—of AD-like neurodegenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several studies have shown that IGF-1 boosts hippocampal neurogenesis [ 106 ], restores spatial memory [ 48 ], and improves depressive-like behaviors through the regulation of serotonin [ 107 ]. Numerous studies have demonstrated that the administration of IGF-1 lessened brain atrophy [ 32 ], brain insulin resistance [ 108 ], apolipoprotein E-related neuropathology [ 109 ], and neurotransmitter secretion [ 110 ]. Other studies have mentioned that IGF-1 improved the long-term survival of hippocampal neurons [ 111 ] and spine maturation [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that IGF-1 boosts hippocampal neurogenesis [ 106 ], restores spatial memory [ 48 ], and improves depressive-like behaviors through the regulation of serotonin [ 107 ]. Numerous studies have demonstrated that the administration of IGF-1 lessened brain atrophy [ 32 ], brain insulin resistance [ 108 ], apolipoprotein E-related neuropathology [ 109 ], and neurotransmitter secretion [ 110 ]. Other studies have mentioned that IGF-1 improved the long-term survival of hippocampal neurons [ 111 ] and spine maturation [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experiments revealed ambiguous shifts in the levels of nerve growth factor (NGF) and insulin-like growth factor (IGF) in brain structures; Aβ (25-35) induced an increase in IGF-1 levels in the hippocampus and cerebral cortex. Although NGF levels slightly increased in the hippocampus, these levels decreased in the cerebral cortex, indicating that sufficient concentrations of growth factors are a prerequisite for neural maturation [ 28 , 29 ]. The ratio of Bax-/Bcl-xL-positive cells increased by 50% in the SVZ and decreased 2.5-fold in the olfactory bulb, indicating the activation of the anti-apoptotic cascade.…”
Section: Discussionmentioning
confidence: 99%